APPLICATION OF NEW DRUGS IN CHRONIC LYMPHOCYTIC LEUKEMIA - Tadeusz Robak (Mediterranean Journal of Hematology and Infectious Diseases)
Over the last few years, several new agents have been under evaluation in preclinical studies as well as in early clinical trials, and have shown promise in treating CLL. These treatments include new monoclonal antibodies (mAbs), immunomodulating agents, novel purine nucleoside analogs, Bcl-2 inhibitors and other agents. The most promising are a new mAbs targeted CD20 molecule or CD23, anti-CD40 mAbs and anti-CD37 antibody. Oblimersen , flavopiridol, and lenalidomide are also being evaluated both in pre-clinical studies and in early clinical trials. However, available therapies are only partially efficient and there is an obvious need to develop better strategies and new, more specific and active drugs